2012
DOI: 10.1002/clc.22060
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Contrast‐Induced Nephropathy With Persistent Renal Dysfunction and Adverse Long‐term Outcomes in Patients With Acute Myocardial Infarction Using the Mehran Risk Score

Abstract: Background: Contrast-induced nephropathy (CIN) has been generally considered to be transient and associated with unfavorable clinical outcomes. Hypothesis: The aim of this study was to investigate whether Mehran risk score could predict CIN with persistent renal dysfunction and long-term clinical outcomes in acute myocardial infarction (AMI) patients undergoing percutaneous coronary intervention (PCI). Methods:We analyzed the clinical data of 1041 AMI patients. The primary end point was defined as major advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 18 publications
1
26
0
2
Order By: Relevance
“…In accordance with the findings of Wi et al [18], Mehran CIN risk score correlated strongly with AKI in our analysis (Fig. 1).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the findings of Wi et al [18], Mehran CIN risk score correlated strongly with AKI in our analysis (Fig. 1).…”
Section: Discussionsupporting
confidence: 93%
“…Preexisting renal impairment, diabetes, congestive heart failure, advanced age, anemia, use of high-contrast medium volume, and a reduced intravascular volume are risk factors for the development of CIN [7,15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Mehran risk score is an important parameter which can predict the risk of CIN in patients with elective coronary procedures and also with acute coronary syndromes. Recently it has been shown that Mehran risk score was also successful in predicting long-term major adverse cardiac event and mortality in acute myocardial infarction patients treated with percutaneous coronary intervention (13).…”
Section: Discussionmentioning
confidence: 99%